Congenital Anomalies of the Upper Extremity Etiology and Management - Laub Jr., Donald R.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2015)
Written by leading experts in the fields of pediatrics, orthopedic surgery, and plastic and reconstructive hand surgery, Congenital Anomalies of the Upper Extremity encompasses the current knowledge of genetic and molecular causes of, and surgical and non-surgical treatment for, deformities of the hand. The book covers the many variations of congenital anomaly encountered in the clinical setting. Embryology, classification, incidence, and anesthesia considerations are discussed first, followed by physical medicine, rehabilitation and therapy management, including psychological considerations, for children living with these conditions. Failures of formation and differentiation of the fingers and hand plate, duplication, and overgrowth, as well as other generalized anomalies, are then presented in detail, including symbrachydactyly, syndactyly, Apert syndrome, polydactyly, amniotic band syndrome, and Madelung deformity, among others. Complete with plentiful photographs and illustrations to guide the clinician in preparing for and performing the necessary treatments, this is an essential book for hand surgeons, orthopedists and plastic surgeons.
Part I. General Considerations -- Embryology and Classification of Congenital Upper Limb Anomalies -- Incidence and Syndromes Associated with Congenital Anomalies of the Upper Limb -- Anesthesia Concerns in Congenital Anomalies of the Upper Extremity -- Physical Medicine and Rehabilitation Management of Children with Congenital Anomalies of the Upper Extremity -- Therapy Management of Children with Congenital Anomalies of the Upper Extremity -- Visible Distinctions and Congenital Anomalies of the Upper Extremities: Psychological Considerations -- Part II. Failure of Formation/Differentiation -- Radial Longitudinal Deficiency: Radius -- Radial Longitudinal Deficiency: Surgical Reconstruction of Congenital Thumb Hypoplasia -- Congenital Radioulnar Synostosis -- Ulnar Longitudinal Deficiency -- Symbrachydactyly -- Dorsal-Ventral Deficiency -- Part III. Failure of Hand Plate Formation/Differentiation -- Syndactyly: A Review of the Current Knowledge on the Genetic Understanding and Management Techniques -- Apert Syndrome -- Central Deficiency (Cleft Hand) -- Camptodactyly and Clinodactyly -- Synostosis and Coalitions of the Hand and Wrist -- Congenital Clasped Thumb -- Part IV. Duplication -- Radial Polydactyly -- Ulnar Polydactyly and Ulnar Dimelia -- Part V. Overgrowth, Amniotic Band, and Generalized Anomalies -- Macrodactyly -- Amniotic Band Syndrome -- Arthrogryposis -- Madelung Deformity -- Epidermolysis Bullosa -- Osteogenesis Imperfecta.
Keywords: Orthopedics; Plastic surgery; Pediatrics; Orthopedics; Plastic Surgery; Pediatrics